2001
DOI: 10.1207/s15326942dn2001_5
|View full text |Cite
|
Sign up to set email alerts
|

Development of Executive Functions Through Late Childhood and Adolescence in an Australian Sample

Abstract: Although there have been significant theoretical advances in the field of child neuropsychology, developmental features of adolescence have received less attention. Progress in clinical practice is restricted due to a lack of well-standardized, developmentally appropriate assessment techniques. This article addresses these issues in relation to executive skills. These abilities are targeted for 2 reasons: first, because they are often considered to be mature during late childhood and adolescence, despite limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
500
4
40

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(586 citation statements)
references
References 34 publications
42
500
4
40
Order By: Relevance
“…That is, fewer errors were made in the late adolescent and young adult age groups irrespective of whether the task required divided attention, selective attention and inhibition of distractors, working memory, or modality switching. Some previous studies have found that different aspects of executive function mature at different rates during adolescence (Anderson, Anderson, Northam, Jacobs, & Catroppa, 2001), but our results imply that more general aspects of executive functioning mature during this time. In sum, our behavioral findings suggest that (a) different measures of executive functioning rely, at least to some extent, on a domain‐general capacity which is already evident during middle adolescence and that (b) this capacity matures from middle adolescence to late adolescence and early adulthood, producing uniform improvements across different executive task types.…”
Section: Discussioncontrasting
confidence: 66%
“…That is, fewer errors were made in the late adolescent and young adult age groups irrespective of whether the task required divided attention, selective attention and inhibition of distractors, working memory, or modality switching. Some previous studies have found that different aspects of executive function mature at different rates during adolescence (Anderson, Anderson, Northam, Jacobs, & Catroppa, 2001), but our results imply that more general aspects of executive functioning mature during this time. In sum, our behavioral findings suggest that (a) different measures of executive functioning rely, at least to some extent, on a domain‐general capacity which is already evident during middle adolescence and that (b) this capacity matures from middle adolescence to late adolescence and early adulthood, producing uniform improvements across different executive task types.…”
Section: Discussioncontrasting
confidence: 66%
“…43 The development of executive function in childhood coincides with maturational growth spurts in the frontal lobes. 44 Early insults in the intrauterine environment may impair the development of neural architecture in the frontal lobes that is necessary for the later development of complex executive functions. 45 IUGR has been demonstrated to lead to a reduction in frontal volume, identifiable through both MRI 46 and sonographic biometric estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ability to control attention remains immature until developments in mid to late adolescents (Anderson et al, 2001), the pattern of poor disengagement found in Study 3 may be characteristic of lonely children and adolescents only; this same pattern of viewing behaviour may not be evident amongst adults whose cognitive skills are more developed (see Puliafico, & Kendall, 2006). Thus, future research should examine the attention biases of lonely adolescents and adults to determine whether there are any changes in attention bias due to cognitive maturity.…”
Section: Implications For Interventionsmentioning
confidence: 90%
“…First, given that cognitive processes develop throughout childhood and adolescence based on neurological changes during this time (Luna, Garver, Urban, Lazar, & Sweeney, 2004), we might expect lonely children to show a different pattern of hypervigilance to social threat compared to adults. For example, compared to adults, children display inferior abilities to consciously relocate attention (Pearson & Lane, 1991;Anderson, Anderson, Northam, Jacobs, & Catroppa, 2001), suggesting that lonely children may be more hypervigilant to social threat than lonely adults and/or show problems of disengagement from (possible) social threats. Given that children do not have mature attentional abilities, findings from the adult literature on HSTH should not be generalised to children.…”
mentioning
confidence: 99%